GFR Decline and Subsequent Risk of Established Kidney Outcomes: A Meta-analysis of 37 Randomized Controlled Trials - Lambers Heerspink, Hiddo J.; Tighiouart, Hocine; Sang, Yingying; Ballew, Shoshana; Mondal, Hasi; Matsushita, Kunihiro; Coresh, Josef; Levey, Andrew S.; Inker, Lesley A. (American journal of kidney diseases, 2014)
The currently established end points for clinical trials of progression of chronic kidney disease (CKD) are end-stage renal disease and doubling of serum creatinine level, which approximates a 57% decline in estimated glomerular filtration rate (eGFR). There is increased interest in using alternative end points in clinical trials to shorten trial duration and reduce sample size. As part of an evaluation of using lesser declines in GFR as alternative end points, we examined the associations of various levels of eGFR decline with the subsequent development of established end points and assess the consistency of alternate levels of eGFR decline across varying clinical manifestations of kidney disease and interventions. Observational analysis of randomized controlled trials. 9,488 participants in 37 randomized controlled trials in CKD. Alternative end points, defined as 30% and 40% declines in eGFR from baseline to month 12. Effect modification by baseline eGFR, proteinuria, cause of disease, and interventions. Established end point, defined as end-stage renal disease, eGFR<15mL/min/1.73m2, or doubling of serum creatinine level. From baseline to 12 months, 16.1% and 7.8% of participants had eGFR declines of ≥30% or ≥40%, respectively. Over a median follow-up of 2.0 (IQR, 1.2-3.1) years after the 12-month baseline period, 2,661 established end points were observed. A strong linear association was observed between eGFR decline and subsequent established end points. HRs for the established end point for 30% and 40% decreases in eGFR compared to a 0% decline were 9.6 (95% CI, 7.3-12.6) and 20.3 (95% CI, 14.1-29.3), respectively. The associations were consistent regardless of baseline eGFR, proteinuria, causes of disease, and interventions. Observational study subject to residual confounding. The strong associations between lesser declines in eGFR and the subsequent development of established end points were consistent across different clinical characteristics of kidney disease and interventions and support implementation of alternative end points in clinical trials of CKD progression.